2022
DOI: 10.1136/jnis-2022-019456
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cerebral aneurysms using artificial intelligence: a systematic review and meta-analysis

Abstract: BackgroundSubarachnoid hemorrhage from cerebral aneurysm rupture is a major cause of morbidity and mortality. Early aneurysm identification, aided by automated systems, may improve patient outcomes. Therefore, a systematic review and meta-analysis of the diagnostic accuracy of artificial intelligence (AI) algorithms in detecting cerebral aneurysms using CT, MRI or DSA was performed.MethodsMEDLINE, Embase, Cochrane Library and Web of Science were searched until August 2021. Eligibility criteria included studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…This step successfully overcame a significant obstacle often faced in brain age model development (i.e. identifying radiological normal scans in a large hospital dataset), resulting in a diverse and realistic set of training data that accurately represents clinical populations (Agarwal et al, 2023; Booth et al, 2023; Din et al, 2023). The diversity of our data, encompassing a range of scanner vendors, acquisition protocols, patient ethnicities, and a wide age span (18–96 years), added robustness to our models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step successfully overcame a significant obstacle often faced in brain age model development (i.e. identifying radiological normal scans in a large hospital dataset), resulting in a diverse and realistic set of training data that accurately represents clinical populations (Agarwal et al, 2023; Booth et al, 2023; Din et al, 2023). The diversity of our data, encompassing a range of scanner vendors, acquisition protocols, patient ethnicities, and a wide age span (18–96 years), added robustness to our models.…”
Section: Discussionmentioning
confidence: 99%
“…However, realising this goal will involve overcoming several challenges. One challenge is the lack of representativeness of research datasets (Agarwal et al, 2023; Agarwal & Wood et al, 2023; Din et al, 2023), particularly public datasets commonly used for training brain age models. This applies not only to the demographics of the study participants, but also to the nature of the MRI data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…25 In a meta-analysis of AI articles on intracranial aneurysm detection, the authors concluded that most studies had a high risk of bias with poor generalizability, with only one-quarter of studies using an appropriate reference standard and only 6/43 studies using an external or hold-out test set. 26 They found low-level evidence for using these AI algorithms and that none of the studies specifically tested for the possibility of bias in algorithm development. 26 In a study that used AI models to detect both intracranial hemorrhage and large-vessel occlusion, the algorithm showed similar excellent performance in diverse populations regardless of scanning parameters and geographic distribution, suggesting that it is unbiased.…”
Section: Primum No Nocerementioning
confidence: 99%
“…26 They found low-level evidence for using these AI algorithms and that none of the studies specifically tested for the possibility of bias in algorithm development. 26 In a study that used AI models to detect both intracranial hemorrhage and large-vessel occlusion, the algorithm showed similar excellent performance in diverse populations regardless of scanning parameters and geographic distribution, suggesting that it is unbiased. 27 This study did not use independent data sets to test that assertion formally.…”
Section: Primum No Nocerementioning
confidence: 99%
“…The IAs are detected via visual assessment of the scans, which is a cumbersome task subject to human error. Even skilled radiologists achieve a rather low sensitivity for small IAs, for instance, from 64 to 74.1% for CTAs (IA diameter ≤ 3 mm) [5] and from 70 to 92.8% (IA diameter ≤ 5 mm) [6], which seems could be achieved or even improved using computerassisted deep learning and artificial intelligence-based approaches [7]. For instance, in a recent study, Yang et al [8] used such a computer-aided aneurysm detection tool and found that 8 out of 649 aneurysms (1.2%) had been overlooked in the initial radiologic reports.…”
Section: Introductionmentioning
confidence: 99%